Factors associated with the quality of sterilization of surgical drapes at the National Hospital University Hubert Koutoukou Maga of Cotonou - Dégbey, Comlan Cyriaque; Madougou, Ibrahim Maman; Sossa, Charles; Dona Ouendo, Edgard-Marius; Makoutode, Michèl (The Pan African medical journal, 2020)
The sterilization of surgical drapes plays an important role in preventing infections associated with treatments. At the CNHU-HKM, sterilization procedure for drapes encounters problems. The purpose of this study was to examine the factors associated with the quality of sterilization of surgical drapes at the CNHU-HKM. We conducted a cross-sectional, descriptive and analytical study focusing on 20 sterile surgical drapes, 41 agents were involved in the management of drapes and 55 members of the surgical team. The probabilistic method was used for sterile surgical drapes, the non-probabilistic method for the others. Pearson's Chi-square Test and logistic regression were used to find the association, with a significant threshold and a p<0.05. Eighty six point forty six percent of subjects were males with an average age of 42 years. The quality of the process of sterilization of the operative drapes was not good in the two departments responsible for processing the drapes. Bacteriological analysis showed that, out of 20 sterile surgical drapes, 9 had Acinetobacter spp. a multidrug-resistant germ causing nosocomial infections. Multivariate analysis showed that professional experience (p=0.015) and quality control of the procedure (p=0.034) were statistically associated with the quality of sterilization. The presence of Acinetobacter spp. on the sterilized drapes demonstrates that sterilization of drapes at the CNHU-HKM is of poor quality. Measures strengthening the skills of providers are necessary to improve the quality of sterilization procedures.